How to make money in stocks success stories : new and advanced investors share their winning secrets - Smith, Amy (McGraw-Hill, 2013)
Proven Methods for Stock Market SUCCESS! "Amy's book is a treasure trove of success stories you should read carefully - each of these investors share what could help you find the top 2% of great stocks."--William J. O'Neil, Chairman & Founder of Investor's Business Daily and author of How to Make Money in Stocks "All you need are one or two great stock in a year and you can achieve some outstanding results." -David Ryan, three-time U.S. Investing Champion Millions of investors around the world have used William O'Neil's bestseller How to Make Money in Stocks as their guide to profiting in the stock market. Now, the most successful investors explain exactly how they have used O'Neil's CAN SLIM method to generate outsized returns. Packed with tips, strategies, lessons, and do's and don'ts, How to Make Money in Stocks Success Stories gives first-hand accounts explaining the ins and outs of applying CAN SLIM in real situations, in the real market. Learn how one woman, with no financial background at all, used the CAN SLIM method to get back on her feet after losing her husband and then shortly after, losing her job; she now invests full time and travels the world. She and many other regular people who have made huge gains with O'Neil's investing method give their first-hand insights that can help anyone who reads this book. "Anyone can become a successful investor," writes Amy Smith. "The success stories in this book will inspire you and show you how to find the market's biggest winners." Whether you're just starting out or have been in the market for years, this hands-on companion to the classic stock investing guide gives you the keys to beating the market on a consistent basis